Genetic characterization and phylogenetic analysis of porcine deltacoronavirus (PDCoV) in Shandong Province, China - Sun, Wenchao (Virus Res, 2020)
Porcine deltacoronavirus (PDCoV) is the etiological agent of acute diarrhoea and vomiting in pigs, threatening the swine industry worldwide. Although several PDCoV studies have been conducted in China, more sequence information is needed to understand the molecular characterization of PDCoV. In this study, the partial ORF1a, spike protein (S) and nucleocapsid protein (N) were sequenced from Shandong Province between 2017 and 2018. The sequencing results for the S protein from 10 PDCoV strains showed 96.7 %–99.7 % nucleotide sequence identity with the China lineage strains, while sharing a lower level of nucleotide sequence identity, ranging from 95.7 to 96.8%, with the Vietnam/Laos/Thailand lineage strains. N protein sequencing analysis showed that these strains showed nucleotide homologies of 97.3%–99.3% with the reference strains. Phylogenetic analyses based on S protein sequences showed that these PDCoV strains were classified into the China lineage. The discontinuous 2 + 3 aa deletions at 400–401 and 758–760 were found in the Nsp2 and Nsp3 coding region in five strains, respectively, with similar deletions having been identified in Vietnam, Thailand, and Laos. Three novel patterns of deletion were observed for the first time in the Nsp2 and Nsp3 regions. Importantly, those findings suggest that PDCoV may have undergone a high degree of variation since PDCoV was first detected in China.